تسوية المنازعات البحرية الناشئة عن الملاحة في مضيق هرمز على ضوء القانون الدولي للبحار والمنظور الإسلامي - فاطمة محمد عبد القادر باقيس
This research discusses the issue of settling maritime disputes arising from navigation in the Strait of Hormuz in the light of the international law of the sea and the Islamic perspective. It explores the peaceful means for settling international maritime disputes by highlighting the role and contribution of the 1982 United Nations Convention on the Law of the Sea in maintaining peace and governance of the sea in the international sphere, and in particular the Arab Gulf region. The strait of Hormuz in considered as one of world’s most important commercial passageway in the Arabian Gulf. Despite its importance, the strait is known to be part of region-wide confrontation and conflict between countries. The problem addressed in this research is highlighted in the shortcomings contained in the rules and provisions of the 1982 Law of the Sea Convention relating to the regulation of international maritime navigation and the settlement of disputes arising from it, as well as the non-joining of some countries to the Convention.This situation exposes the area to risks arising from international maritime disputes threatening the safety of international navigation. To achieve the objectives of the research, the researcher applies both descriptive and analytical methodology in order to describe and analyze legal texts, cases, journal articles and literatures related to navigational disputes and maritime law. Islamic primary sources of authentic texts, classical jurisprudential writings, articles and literatures are referred to in analyzing the Islamic perspective on the situation in the Strait of Hormuz. This research proposes a holistic approach in highlighting the revisited role of the 1982 United Nations Convention on the Law of the Sea in the context of the Strait of Hormuz. It also encourages observation and cooperation of states on the United Nations effort to implement the principle of peaceful settlement of international maritime disputes, which stems from states’ obligation to apply the principle of prohibiting the use or threat of force in the framework of international relations. This research also advocates the need for all countries concerned with international maritime navigation in the Strait of Hormuz to hold international consensus by way of conferences to set the rules, provisions and controls that regulate the process of navigation through the strait, provided that they are acceptable to all, and that they do not threaten or impede maritime navigation in the strait. It also highlights the necessity of strengthening the means of settling international maritime disputes on the basis and rules of diplomatic action, and based on the principles contained in international maritime law, and continuous effort to develop and ratify the relevant international conventions in the field of regulating international maritime affairs on the strait.